1989
DOI: 10.1080/00150198908014284
|View full text |Cite
|
Sign up to set email alerts
|

Stark effect of14N NQR in single crystals of ferroelectric NaNO2

Abstract: The effects of the external electric field on 14N nuclear quadrupole resonance (NQR) have been investigated in the ferroelectric phase of sodium nitrite (NaNO,) single crystals with either the single domain or the multidomain structure. NQR measurements of two resonance lines of v + and u -were made at 77 K under the external electric field up to 25 kV/cm. The rates of the Stark shift in the crystal of single domain are du+/dE+ = 6.8 f 3.0, dv'ldE-= -9.8 f 2.2, dv-ldE' = 5.0 f 2.0, and dv-/dE-= -2.5 f 2.4 Hz .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Since the electric field gradients at the two 14 times those previously reported for NaN0 2 [8,9] and listed in Table 2.…”
Section: B) Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Since the electric field gradients at the two 14 times those previously reported for NaN0 2 [8,9] and listed in Table 2.…”
Section: B) Resultsmentioning
confidence: 78%
“…Experimental evidence [5,8,9] revealed that the shift of NQR frequency is up (down) for £ + (£_) with respect to the spontaneous polarization. When an electric field is applied to a crystal for NQR measurements, a polarization is induced; the electric field applied along the ferroelectric axis increases (reduces) the P s of the crystal for E^P S {EUP S ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations